Iron will eaudiobook - Loveling, Daphne (Lords of Carnage: Ironwood MC, 2020)
Biker. Criminal. Bastard. Rourke Powers is all those things, and more. To say we come from different worlds is an understatement. I'm ambitious. Professional. I keep my nose clean and my reputation impeccable. No bad choices. No bad boys. The VP of the Ironwood Lords of Carnage? Definitely not part of the plan. But when fate slams us together, to protect someone we both care about, it's impossible to deny the heat between us. Whoever said opposites attract? They're not wrong. He's confident and cocky. Deliciously dangerous. Definitely doable. He's fire to my ice. Bad boy to my good girl. Unfortunately for me, he's damn near irresistible. But I will resist him. I have to. I know from bitter experience, men in general can't be trusted. Even the ones who look squeaky clean can harbor dark secrets underneath. And Rourke? He doesn't even try to hide his dangerous side. I'm so tempted to give him my body. But I'll never trust Rourke with my heart. Contains mature themes.